Perencanaan Keuangan Dan Implementasi Praktik Investasi Pada Umkm Di Desa Limbangan Barat Kabupaten Garut - Pratama, Vidya Ramadhan Putra (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze and explain the direct and indirect effects of competence, motivation, and organizational culture on employee performance, with leadership style as a moderating variable. The research is descriptive and confirmatory, conducted through field data collection using descriptive survey and explanatory survey methods. The unit of analysis consists of 150 employees at the National Counter-Terrorism Agency (BNPT). Data analysis was performed using multiple regression analysis with Smart PLS. The results indicate that competence and motivation do not have a direct effect on employee performance, while organizational culture has a positive and significant effect. Leadership style does not moderate the relationship between competence and employee performance, but significantly moderates the relationship between motivation and performance. Additionally, leadership style does not moderate the relationship between organizational culture and employee performance.